PERSEPSI MAHASISWA PENDIDIKAN MATEMATIKA TENTANG PELAKSANAAN MAGANG TERAPAN OLEH STKIP MPL TAHUN AKADEMIK 2015-2016 - Noerhasmalina, Noerhasmalina; Astuti, Robia (JURNAL e-DuMath, 2018)
AbstractÂ In the academic year 2015-2016 for the first time STKIP Muhammadiyah Pringsewu Lampung (STKIP MPL) implementing Applied Internship program (MT). Applied internship is mandatory for students after graduation internship Basic (MD) and the Advanced Apprenticeship (ML). MT This is a new program and the suspect will be perceived together with Field Experience Practice program (PPL). The purpose of this study was to describe the mathematics education students perceptions about the implementation of MT by STKIP MPL. The population in this study were all students STKIP MPL trainees applied consisting of four courses. Determination of the study sample was using technique purposive sampling. Retrieved mathematics education courses as a sample followed by 60 participants. To obtain data on students perceptions conducted questionnaire. Furthermore, the data were analyzed descriptively. Based on the analysis and discussion of the perception expressed obtained 7 student interns applied academic year 2015-2016.Â Keywords:.Applied Internship, Student Perceptions